The validation of project management reference framework using rasch model - Mohd Firdaus Mustaffa Kamal,; Haryanti Mohd Affandi,; Adam Aruldewan S. Muthuveeran,; Nasyairi Mat Nasir, (Penerbit Universiti Kebangsaan Malaysia, 2023)
A project management reference framework has been developed to deal with the scarcity of a commonly recognized term of reference for Malaysian public project management. The development of this framework was instigated by the lack of terms of reference for the practice to generate the key competencies that public project managers should acquire. In this study, a working framework has been validated using the RASCH measurement model to see whether the construct identified is fit to be included within the framework. A Questionnaire survey has been used for data collection. The sample chosen was from G7 construction companies registered with CIDB and government organizations involved with construction projects. Data has been analyzed using dimensionality test and item fit testing. Through the analysis, the construct, which consists of twenty-four significant activities, has been identified to be included in the five major phases of the project lifecycle, namely the inception stage, design stage, tendering stage, construction stage, and closeout stage. With this analysis, a working Project Management Reference Framework has been validated and hopefully beneficial to the industry’s practitioner.